PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DI UD. ANGGREK TELUK DALAM - Duha, Dita Susanti (Universitas Nias Raya, 2025)
The aim of this research is to determine the effect of service quality on consumer loyalty at UD. Telukdalam Orchid, South Nias Regency. The type of research used is quantitative, the data source is consumers, with the population and sample in this research being all consumers who buy at UD. Telukdalam Orchid. Data collection techniques are questionnaires and documentation. The data analysis method used is simple linear regression analysis. The research results show that the tcount value is 6.136>ttable 2.024. So it is concluded that there is a positive and significant influence of service quality on consumer loyalty at UD. Telukdalam Orchid. The suggestion of this research is (1) To improve service quality to build customer loyalty at UD. Anggrek Telukdalam is by providing fast and timely service to consumers, so that customers will make purchases regularly and be more satisfied with the services provided. (2) In an effort to improve services, UD should improve. Aggrek provides training and direction to employees so that they can be more responsive at work, especially in providing assistance to consumers who drive when shopping. (3) UD. Anggrek should provide training to employees to master the types of products sold so that employees can serve consumer demand well. (4) In an effort to increase customer loyalty, UD. Orchids need to pay attention to the price and quality of products sold to consumers so that consumers do not make purchases in other stores.